Editors' Note: Association of Statins With Cerebral Atherosclerosis and Incident Parkinsonism in Older Adults. (27th September 2022) - Siegler, James E.; Galetta, Steven
Abstract : Using consolidated data from 3 observational cohort studies of elderly individuals, Dr. Oveisgharan et al. evaluated the relationship between statin use and the development of incident parkinsonism and intracranial atherosclerosis. Parkinsonism was determined on clinical grounds if ≥2 elements of the Unified Parkinson's Disease Rating Scale were identified, and intracranial atherosclerosis was assessed on postmortem fixation of the large intracranial vessels using a semiquantitative scale reflecting plaque burden. Statin use was protective against both atherosclerosis and incident parkinsonism, with atherosclerosis mediating 17% of the risk of parkinsonism in the cohort. In response, Dr. Keller cites the preliminary results of the PD-STAT trial that failed to show simvastatin was superior to placebo at slowing the rate of Parkinson disease. Dr. Oveisgharan et al. highlight that their findings indicate statin reduced the risk of incident parkinsonism, rather than reduced progression of parkinsonian symptoms. Future trials involving a larger sample size are called on, which will test the effect of statins on patients with Parkinson disease—particularly those with concomitant intracranial atherosclerosis.